Efficacy of Nifedipine in Preterm Labor for Prolongation of Pregnancy for at Least 48 Hours - Jabbar, Hira; Maqsud, Mahliqa; Haq, Bushra; Sarfaraz, Rehana (Indus Journal of Bioscience Research, 2025)
Introduction: The occurrence of preterm labor during the first 37 weeks of pregnancy creates substantial risks to newborns, which requires effective tocolytic treatments. The calcium channel-blocking drug Nifedipine serves as a common medication for pregnancy delay to enable corticosteroid administration as well as maternal transfer to advanced care centers (1). Objective: This study determines how nifedipine affects maternal-neonatal outcomes while measuring its ability to extend pregnancy more than 48 hours in women experiencing preterm labor. Materials and Method: The study was conducted from 1st August, 2024 to 31st January, 2025 in Unit 2 of Services Hospital, Lahore and accepted 78 women from 15 to 40 years’ old who were carrying single baby fetuses between 28–34 weeks + 5 days. The patients received nifedipine by mouth, starting with 20 mg as a loading dose, followed by up to 160 mg daily over 48 to 72 hours. Data were analyzed using SPSS 20.0 (p<0.05). Results: The duration of Nifedipine treatment Treated 64 women during labor for more than 48 hours (82.1%), but age, gestational age, and parity did not create any essential differences (p>0.05).